The Development of Image Overlay System in Biomedical Application - Asrani, Lit; Muhammad Irfan, Abdul Rahman; Fariza, Mahyan (LAP LAMBERT Academic Publishing, 2016)
Image overlay system is a computer display technique which an image superimposes another image to create a variable result. This technique can be applied in the biomedical field. During surgery process, there is the limitation of visualization to see both surface and the inside of the patient at the same time. The surgeon also has limited variable of an image for early diagnosis. Image overlay system will help the doctor with providing the image for early diagnosis to assist the doctor. With MATLAB as a software platform, the image overlay system can be generated faster to process the image and do not consume longer time. The output image can be adjusted their transparency level and the type of “colormap” which is very helpful for the doctor. With the development of graphical user interface (GUI), this system can be handled easily for the new user.